Free vibration analysis of laminated composite plates based on higher order shear deformation theory by using finite element method - Ibrahim, Mohd Sultan; Ismail, Ahmad Faris; Khan, Md. Raisuddin (2002)
The present work deals with free vibration analysis of laminated composite plates using a present higher order displacement model. The present model is tested on the evaluation of free vibration of laminated composite plates in order to illustrate the deficiency of the classical plate theory and the first order shear deformation theory. The present work is also aimed at conducting a parametric study to investigate the frequency response of laminated composite plates for different material properties, number of layers, fiber orientations, boundary conditions and side to thickness ratios. A finite element computer code was developed and implemented to carry out the work.